The ultimate competitive advantage : why your people make all the difference and the 6 practices you need to engage them - Moon, Shawn D. (Shawn Daniel), 1967- (Dallas, TX : BenBella Books, 2015)
''People are our most important asset.' Every company pays lip service to this platitude, but how many companies really embrace it? What happens when everyone in your company is truly engaged and functions as a genuine leader? Every move your company makes can be copied by your competitors. New facilities, improved processes, product innovations, and marketplace initiatives can all be important, but rarely lead to sustained competitive advantage-because other businesses can just follow suit or piggyback off your progress. But truly mobilizing your people creates positive results in a thousand different ways throughout your organization, giving your company the ultimate competitive advantage-an advantage that is very difficult to match. It's not easy to fully engage everyone in your organization, to create an organization of people who act as leaders, take initiative, and operate from a strategic perspective. But it can be done, and no one knows more about achieving this than FranklinCovey. For decades, FranklinCovey has been working with businesses throughout the world to train their people in the seven habits model of personal effectiveness. They've learned how to take this training to the next level, to dramatically improve the effectiveness of not just individuals, but entire organizations. The Ultimate Competitive Advantage describes the six practices FranklinCovey has discovered to engage people across the company, and shows how employing these practices can take your organization to a higher level of performance. In the end, the success of any organization is dependent on effectiveness and the commitment of its people. Everyone knows this, but few organizations operate this way. But, with the help of The Ultimate Competitive Advantage, yours can'--
Keywords: Leadership; Corporate culture; Organizational behavior; Organizational effectiveness; Employee motivation